2022
DOI: 10.1002/dta.3232
|View full text |Cite
|
Sign up to set email alerts
|

Potential of chromatography and mass spectrometry for the differentiation of three series of positional isomers of 2‐(dimethoxyphenyl)‐N‐(2‐halogenobenzyl)ethanamines

Abstract: N-(2-substituted benzyl)-2,5-dimethoxyphenethylamines often cause severe poisonings which has led to their legal prohibition in many countries. At the same time, their positional isomers can be studied as potential therapeutic drugs. In this regard, the search for various approaches to differentiate these isomers is an important practical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The drugs were purified using flash chromatography on high-purity Merck silica gel (9385, 60 Å, 230–400 mesh), yielding white powder hydrochlorides. Analytical data used in this study was reported previously. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drugs were purified using flash chromatography on high-purity Merck silica gel (9385, 60 Å, 230–400 mesh), yielding white powder hydrochlorides. Analytical data used in this study was reported previously. , …”
Section: Methodsmentioning
confidence: 99%
“…Testing their acute behavioral and neurochemical effects, we have previously identified four interesting neuroactive compounds for further analyses (Figure ), including two compounds with pronounced beneficial (anxiolytic/antidepressant-like) acute behavioral effects with increased brain serotonin and dopamine turnover ( N -(2-trifluoromethoxybenzyl)-2-(2,4-dimethoxyphenyl)­ethylamine, 24H-NBOMe­(F)) and N -(2-trifluoromethoxybenzyl)-2-(3,4-dimethoxyphenyl)­ethylamine, 34H-NBOMe­(F)), one compound with anxiogenic-like profile but no overt neurochemical profiles ( N -(2-fluorobenzyl)-2-(3,4-dimethoxyphenyl)­ethylamine, 34H-NBF) acutely, and a behaviorally inert compound with overt neurochemical activity similar to 24H-NBOMe­(F) and 34H-NBOMe­(F), N -(2-chlorobenzyl)-2-(3,4-dimethoxyphenyl)­ethylamine (34H-NBCl). Their ability to cross the zebrafish blood-brain barrier and enter the brain as well as chemical synthesis, chemical structures, and analytical data have already been reported previously. Typically, in the 25X-NBOMe conventional nomenclature, the X (i.e., H for hydrogen here) indicates the substitution at position 4 of the phenethylamine moiety. , However, as 24H- and 34H- isomers carry a methoxy group at this position, they can also be described as 24- and 34-NBOMes, respectively . Here, we will specifically use the latter nomenclature, aiming at a greater clarity in order to emphasize that no other substitutions (beyond the two methoxy groups) were introduced at the phenyl ring of the phenethylamine moiety (also see similar examples in refs , , and ).…”
Section: Introductionmentioning
confidence: 99%